Вывод СВЧ-энергии из резонатора управляемой трансформацией вида колебаний; Известия вузов. Физика; Т. 57, № 12/2 - Игумнов В. С. Владислав Сергеевич; Августинович В. А. Владимир Андреевич; Артеменко С. Н. Сергей Николаевич; Юшков Ю. Г. Юрий Георгиевич (2014, 2014)
Заглавие с экрана